A pyrazine bis-adduct of a binuclear rhodium(II) carboxylate containing 3,4,5-triethoxybenzoate as the equatorial ligand - Castro, María A. (2002)
The title compound, tetrakis(μ-3,4,5-triethoxybenzoato-κ2O:O′)bis[(pyrazine-κN)rhodium(II)](Rh—Rh), [Rh2(C13H17O5)4(C4H4N2)2], crystallizes on an inversion centre in the triclinic space group P ‾1. The equatorial carboxylate ligands bridge the two RhII atoms, giving a binuclear lantern-like structure. The pyrazine molecules occupy the two axial coordination sites. The phenyl rings are tilted by ca 10° with respect to the attached carboxylate groups. The pyrazine planes have a torsion angle of ca 19° around the Rh—N bond with respect to the plane of the nearer carboxylate group and are not coplanar with the Rh—Rh bond.